The effect of non-teacher unit costs on students’ performance in KCSE examinations in public secondary schools in Kenya - James Ochieng Sika; Fredrick Ogweno Nyawanda (S&Co Publishing, 2024)
In Kenya, non–teacher unit cost has a bearing on academic performance. Although there are conflicting views on studies on non- teacher unit costs and its effect on academic performance, recent studies show that increases in resources have a modest positive effect on academic performance. However, it is noted that schools in Vihiga Sub-County charge twice Ministry of Education recommended fee guidelines yet the Sub-county still has the lowest KCSE (Kenya Certificate of Secondary Education) Mean Score of 5.361 (grade C-) which is below the minimum tertiary entrance. The purpose of this study was therefore to find out why students in public secondary schools in Vihiga Sub-County perform poorly in KCSE examination despite the high non- teacher unit costs. The study used ex post facto and descriptive survey design. The study population consisted of 21 head teachers and 350 teachers in 21 public secondary schools and one Sub-County Director of Education in the Sub-County. A sample of 18 head teachers and 307 teachers in 18 public secondary schools and one Sub-County Director of Education in the Sub-County were selected for the study using a saturated sampling method. Data was collected using questionnaires, document analysis and interview schedules. The findings of this research show that there is significant effect of non-teacher unit cost and on KCSE examinations in Vihiga Sub County. Hence there is need for the government to increase funding of the non-teacher aspect of education.